2020
DOI: 10.1016/j.drudis.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine against malaria, cancers and viral diseases

Abstract: Graphical abstract The pleiotropic effects of chloroquine that including anti-malaria, anti-cancer and anti-viral diseases, which is linked with inhibition of autophagy, tumor vascular normalization, lysosomotropic and immunomodulatory property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 107 publications
(105 reference statements)
1
49
0
Order By: Relevance
“…Nowadays, chloroquine and hydroxychloroquine are used to treat autoimmune and connective tissue diseases like systemic lupus erythematosus (SLE), rheumatoid arthritis, Sjögren's syndrome, sarcoidosis, palindromic rheumatism, eosinophilic fasciitis, dermatomyositis, cellulitis, mixed and undifferentiated connective tissue disease (11,13,14). They have also demonstrated anticancer properties against different types of cancer (e.g., colon, lung and breast cancer, central nervous system tumors, hematological malignancies), and against cancer cell lines in vitro (11,15). CQ has also demonstrated antiviral activity, and has been used in clinical trials in infections caused by hepatitis C virus, dengue virus-2, human immunodeficiency virus, and Chikungunya virus (15).…”
Section: Clinical Applications Of Antimalarial Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, chloroquine and hydroxychloroquine are used to treat autoimmune and connective tissue diseases like systemic lupus erythematosus (SLE), rheumatoid arthritis, Sjögren's syndrome, sarcoidosis, palindromic rheumatism, eosinophilic fasciitis, dermatomyositis, cellulitis, mixed and undifferentiated connective tissue disease (11,13,14). They have also demonstrated anticancer properties against different types of cancer (e.g., colon, lung and breast cancer, central nervous system tumors, hematological malignancies), and against cancer cell lines in vitro (11,15). CQ has also demonstrated antiviral activity, and has been used in clinical trials in infections caused by hepatitis C virus, dengue virus-2, human immunodeficiency virus, and Chikungunya virus (15).…”
Section: Clinical Applications Of Antimalarial Drugsmentioning
confidence: 99%
“…They have also demonstrated anticancer properties against different types of cancer (e.g., colon, lung and breast cancer, central nervous system tumors, hematological malignancies), and against cancer cell lines in vitro (11,15). CQ has also demonstrated antiviral activity, and has been used in clinical trials in infections caused by hepatitis C virus, dengue virus-2, human immunodeficiency virus, and Chikungunya virus (15). Recently, CQ and CHQ were proposed as treatments for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection and were prescribed for almost 12% of COVID-19 patients in Europe (16).…”
Section: Clinical Applications Of Antimalarial Drugsmentioning
confidence: 99%
“…As an adjuvant, CQ was shown to enhance clinical responses to anti-GBM therapy in double-blinded Phase III studies 68 . CQ was shown to be able to cross the blood-brain barrier in vivo 69–71 , while preclinical studies have demonstrated that concentrations of 50 mg/kg are suitable for administration regimens against orthotopic glioblastoma xenografts 72–74 . The multiple effects of CQ on the phenotypic signatures and chemokine profiles of GBM in vivo , alongside a limited ability to control tumor burden alone, however, point to a nuanced role in combination regimens which can nonetheless uniquely enhance CAR-based adoptive transfer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As a new emerging hCoV, it is largely unknown how SARS-CoV-2 is targeted by or manipulates autophagy. Accumulating evidence suggests that SARS-CoV-2 infection may perturb the autophagic process ( localization [70,71]. It is doubtful that their putative effects on autophagy inhibition are necessarily causal for their anti-SARS-CoV-2 activity in specific cells.…”
Section: Sars-cov-2 Infection and Autophagymentioning
confidence: 99%
“…Unfortunately, their inhibitory efficiency did not extend to SARS-CoV-2 infected TMPRSS2-expressing human lung cells or animal models and COVID-19 patients [ 66–69 ]. It should be noted that lysosomotropic agents CQ and HCQ have many physiological functions, including blocking autophagosome-lysosome fusion, alkalizing endosomal/lysosomal acidification, and disrupting lipid clustering and ACE2 localization [ 70 , 71 ]. It is doubtful that their putative effects on autophagy inhibition are necessarily causal for their anti-SARS-CoV-2 activity in specific cells.…”
Section: Targeting Autophagy As a Promising Strategy For Covid-19mentioning
confidence: 99%